2016
DOI: 10.1371/journal.pone.0154084
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Maize Canopy Development as Affected by Increased Plant Density

Abstract: Improving crop productivity through higher plant density requires a detailed understanding of organ development in response to increased interplant competition. The objective of this paper is thus to investigate the characteristics of organ development under increased interplant competition. A field experiment was conducted to investigate organ development across 4 maize plant densities i.e. 2, 6, 12 and 20 plants m–2 (referred to PD2, PD6, PD12 and PD20 respectively). In response to increased interplant compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…This suggested that as plant density increases, increased interplant competition restricts the growth of reproductive sink capacity (Hashemi, Herbert, & Putnam, ; Sarlangue, Fernando, Andrade, Calviñ, & Purcell, ; Vega, Andrade, Sadras, Uhart, & Valentinuz, ; Westgate, Forcella, Reicosky, & Somsen, ), thereby resulting in smaller cobs, increased barrenness and hence lower yields. Interplant competition also shown to affect plants organ growth and development (Song, Rui, Bedane, & Li, ) may have also impact on plant productivity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that as plant density increases, increased interplant competition restricts the growth of reproductive sink capacity (Hashemi, Herbert, & Putnam, ; Sarlangue, Fernando, Andrade, Calviñ, & Purcell, ; Vega, Andrade, Sadras, Uhart, & Valentinuz, ; Westgate, Forcella, Reicosky, & Somsen, ), thereby resulting in smaller cobs, increased barrenness and hence lower yields. Interplant competition also shown to affect plants organ growth and development (Song, Rui, Bedane, & Li, ) may have also impact on plant productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Whole plant canopy level effects indicated that through local responses that may vary with positions in different types of organs [28, 34,35]. For example, the effect of plant density on leaf area expansion through two parts i.e., lamina length and lamina width, the first being consistently decreased in both lower and upper phytomers [36] whereas the second being increased in lower phytomers and decreased in upper phytomers [37]. Increasing panting density accelerated leaf senescence [38], increased the shading of leaves [18], and reduced the net assimilation of individual plants.…”
Section: Plant Density Effect On Canopy Morphology Of Maize Cropmentioning
confidence: 99%
“…Differential effects on leaf length and leaf width have been observed in response to plant density in maize (Sonohat & Bonhomme ). Furthermore, leaf width variations have been shown to closely match the decrease in light interception per plant with plant density (Fournier et al ), whereas leaf length may respond positively or negatively to increased density depending on leaf rank (Sonohat & Bonhomme ; Song et al ). This suggests independent effects of light and water limitations.…”
Section: Introductionmentioning
confidence: 99%